STRATEGI GURU DALAM MENANAMKAN NILAI KERUKUNAN ANTAR UMAT BERAGAMA DISEKOLAH DASAR - Nurmayani, Nurmayani; Putri, Zuhti Atitta; Nasywa, Nabila; Yusuf, Liza Aulia; Abrilya, Selsy; Nasution, Nisya Sazwana (Jurnal Merah Putih Sekolah Dasar, 2026)
This study aims to describe the state of interfaith harmony at Pelangi Elementary School, identify inhibiting factors, and design strategies for teachers to instill the values of harmony in elementary schools. The approach used is descriptive qualitative with data collection techniques including observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and drawing conclusions based on the Miles and Huberman model.The results of the study indicate that harmony among students has not been optimal. Students still tend to interact with peers of the same religion, their understanding of tolerance is still superficial, there are no structured programs to foster harmony, and there is an influence from the family environment that does not sufficiently support inclusive attitudes. To address this, teachers can implement various strategies, including integrating the values of tolerance into the learning process, forming heterogeneous study groups, and organizing thematic programs like Harmony Day and interfaith social projects. In addition, parental and community involvement is essential to strengthen students’ inclusive attitudes. Teachers should also serve as role models in daily life so that students can learn from real examples. These strategies are expected to create an inclusive and harmonious school environment while fostering tolerance from an early age.